Intraoperative Incisional Wound Irrigation with 0.05% Chlorhexidine versus 0.9% Saline to Prevent Surgical Site Infection after Laparotomy for Hollow-Viscus Perforation Peritonitis: A Double-Blind Randomized Controlled Trial - Oktova Ardianto; Bambang Am Am Setya Sulthana; Rizki Diposarosa (HM Publisher, 2026)
Background: Surgical site infection (SSI) is the most frequent complication of abdominal surgery and a major source of morbidity, prolonged hospitalization and cost, particularly in dirty (class IV) wounds created by gastrointestinal perforation; intraoperative incisional irrigation may lower wound bioburden, yet the optimal irrigant is undefined. Methods: We conducted a double-blind randomized controlled trial at a tertiary referral center in Bandung, Indonesia (November 2019–August 2020) comparing incisional irrigation with 0.05% chlorhexidine versus 0.9% saline in adults undergoing emergency laparotomy for hollow-viscus perforation peritonitis. After fascial closure, incisions were irrigated by allocation and patients were followed for 30 days, with superficial SSI (ASEPSIS score) as the primary outcome. Results: Of 141 patients screened, 96 were analyzed (49 chlorhexidine, 47 saline). Superficial SSI occurred in 5/49 (10.2%) chlorhexidine versus 14/47 (29.8%) saline patients (χ²=5.795, p=0.016; Fisher exact p=0.021; OR 0.268, 95% CI 0.088–0.818; relative risk 0.343; absolute risk reduction 19.6%; number-needed-to-treat 5.1). In multivariable logistic regression, chlorhexidine remained independently protective (adjusted OR 0.228, 95% CI 0.062–0.836, p=0.026), while intra-abdominal contamination (aOR 1.377 per 100 mL, p=0.008) and operative time (aOR 1.645 per 30 min, p=0.027) increased risk; the model discriminated well (AUC 0.835). No irrigation-related adverse events occurred. Conclusion: Incisional irrigation with 0.05% chlorhexidine markedly reduced superficial SSI after laparotomy for perforation peritonitis and offers a low-cost strategy for dirty abdominal wounds.